Development of the "Al-muhdastah Al-yaumiyyah" Textbook to Improve Arabic Speaking Skills at an Islamic Boarding School - Agus Yasin; Marheni Br Maha; Fahrurrozi; Ahmad Hidayatullah Zarkasyi; Siti Anne Barkah Nur Fauziah; Ahmad Zalzuli (Izdihar : Journal of Arabic Language Teaching, Linguistics, and Literature, 2023)
This study aimed to improve Arabic speaking skills textbooks which were developed in such a way that interactive exercises and topics were adapted to the student’s language by adding appropriate vocabulary and pictures to the learning material. This research was used as a template for ADDIE's research and development (R&D). The study sample was first-grade students at the Mawaridussalam Islamic Boarding School, with class 1C (30 students) used to assess student interest and the textbooks’ effectiveness. The data were collected by observations, interviews, and tests before qualitative and quantitative analyses. The significance of the average student’s test score after using the designed textbook (80.50) was higher than the average score before using the textbook (59.17) to learn Arabic speaking skills. These results confirmed that the proposed educational approach is practical, simple, and attractive.